"Wax On, Wax Off": In Vivo Imaging of Plant Physiology and Disease with Fourier Transform Infrared Reflectance Microspectroscopy. Issue 19 (2nd August 2021) - Khambatta, Karina; Hollings, Ashley; Sauzier, Georgina; Sanglard, Lilian M. V. P.; Klein, Annaleise R.; Tobin, Mark J.; Vongsvivut, Jitraporn; Gibberd, Mark R.; Payne, Alan D.; Naim, Fatima; Hackett, Mark J.
Abstract: Analysis of the epicuticular wax layer on the surface of plant leaves can provide a unique window into plant physiology and responses to environmental stimuli. Well‐established analytical methodologies can quantify epicuticular wax composition, yet few methods are capable of imaging wax distribution in situ or in vivo. Here, the first report of Fourier transform infrared (FTIR) reflectance spectroscopic imaging as a non‐destructive, in situ, method to investigate variation in epicuticular wax distribution at 25 µm spatial resolution is presented. The authors demonstrate in vivo imaging of alterations in epicuticular waxes during leaf development and in situ imaging during plant disease or exposure to environmental stressors. It is envisaged that this new analytical capability will enable in vivo studies of plants to provide insights into how the physiology of plants and crops respond to environmental stresses such as disease, soil contamination, drought, soil acidity, and climate change. Abstract : Fourier transform infrared (FTIR) reflectance spectroscopic imaging has been used to image epicuticular waxes on the surface of plant leaves, in living plants, to observe how plant physiology changes in response to environmental stressors or disease.